The Outcomes and Patterns of Treatment Failure After Surgery for Locally Recurrent Rectal Cancer. Issue 2 (August 2016) - Harris, Craig A.; Solomon, Michael J.; Heriot, Alexander G.; Sagar, Peter M.; Tekkis, Paris P.; Dixon, Liane; Pascoe, Rebecca; Dobbs, Bruce R.; Frampton, Chris M.; Harji, Deena P.; Kontovounisios, Christos; Austin, Kirk K.; et al.
Abstract : Objective: To assess the outcomes and patterns of treatment failure of patients who underwent pelvic exenteration surgery for recurrent rectal cancer. Background: Despite advances in the management of rectal cancer, local recurrence still occurs. For appropriately selected patients, pelvic exenteration surgery can achieve long-term disease control. Methods: Prospectively maintained databases of 5 high volume institutions for pelvic exenteration surgery were reviewed and data combined. We assessed the combined endpoints of overall 5-year survival, cancer-specific 5-year mortality, local recurrence, and the development of metastatic disease. Results: Five hundred thirty-three patients who had undergone surgery for locally recurrent rectal cancer were identified. Five-year cancer-specific survival for patients with a complete (R0) resection is 44%, which was achieved in 59% of patients. For those with R1 and R2 resections, the 5-year survival was 26% and 10%, respectively. Radical resection required sacrectomy in 170 patients (32%), and total cystectomy in 105 patients (20%). Treatment failure included local recurrence alone in 75 patients (14%) and systemic metastases with or without local recurrence in 226 patients (42%). Chemoradiotherapy before exenteration was associated with a significant ( P < 0.05) improvement in overall 5-year cancer-specific survival for those patients with an R0 resection. Postoperative chemotherapy did not alter outcomes. Conclusions: R0 resection of the pelvic recurrence is the most significant factor affecting overall and disease-free survival. The surgery is complex and often highly morbid, and where possible patients should be given perioperative chemoradiotherapy. Further investigations are required to determine the role of adjuvant chemotherapy.